Limiting the Application of the Exclusionary Rule: The Good Faith Exception - Brinegar, Meredith B. (1981)
The Supreme Court does not believe that the deterrent value of the exclusionary rule is sufficiently well established to merit broadening the rule's scope. The Court nonetheless has not yet carved out a blanket exception to the rule based solely on a lack of deterrent value. The Fifth Circuit decided in Williams that the exclusionary rule is not an effective deterrent in the good faith mistake or technical violations cases. It therefore removed these fourth amendment violations from exclusionary rule doctrine. Although the Fifth Circuit correctly reasoned that the Supreme Court would support the exception in the case of police reliance on a statute later declared unconstitutional, the Fifth Circuit went too far in holding that deterrence considerations and Supreme Court precedent supported inclusion of good faith mistakes within the ambit of the exception